Activation of Kv7 channels with the anticonvulsant retigabine alleviates neuropathic pain behaviour in the streptozotocin rat model of diabetic neuropathy. (26th November 2019) - Djouhri, Laiche; Malki, Mohammed Imad; Zeidan, Asad; Nagi, Karim; Smith, Trevor
Abstract: Diabetic peripheral neuropathy (DPN) is the most incapacitating complication of diabetes mellitus. Up to 50% of patients with DPN develop peripheral neuropathic pain (PNP). The underlying ionic and molecular mechanisms of diabetic PNP (DPNP) are poorly understood. However, voltage gated potassium (Kv 7) channels which have been implicated in the pathogenesis of other types of PNP are likely to be involved. Here we examined, in the streptozotocin (STZ) rat model of DPNP, whether activating the Kv7 channels with a potent activator retigabine (ezogabine) would reverse/attenuate behavioural signs of DPNP. STZ rats exhibited behavioural indices of mechanical and heat hypersensitivity, but not cold hypersensitivity or spontaneous pain, 35 days after STZ injection. Retigabine given at a dose of 15 mg/kg (but not at 7.5 mg/kg, i.p.) significantly attenuated mechanical, but not heat hypersensitivity in DPNP rats, and was as effective as the positive control gabapentin. This analgesic effect of retigabine was completely reversed by the Kv 7/M channel blocker XE991 (3 mg/kg, i.p.) indicating that the anti-allodynic effects of retigabine were mediated by Kv 7 channels. In conclusion, the findings suggest that Kv7 channels are involved in DPNP pathogenesis, and that strategies that target their activation may prove to be effective in treating DPNP.